Celebrating Pedagogical Ideas - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2001)
A decription of a conference on education reform in Lithuania.
Keywords: Department of Education; scientific conference; education reform; L. Jovaiša.